Rancang bangun sistem pemantauan dan penyiraman pintar tanaman cabai pada greenhouse menggunakan Fuzzy Mamdani berbasis Blynk IoT - Arief, Zainal; Zarory, Hilman; Jufrizel , Jufrizel; Mursyitah, Dian (Fakultas Teknologi Informasi Universitas Kristen Satya Wacana, 2024)
One of the leading horticultural commodities cultivated by farmers is chili. However, chili farmers often experience problems monitoring soil moisture levels and environmental air temperature. In this case, it can affect the growth of chili plants, which impacts crop failure. Therefore, to overcome these problems, this research develops Mamdani fuzzy logic to build an intelligent system that can automatically monitor and water chili plants. In this research, the impact of the use of sensors and system impact treatment on chili plants will be tested and compared with plants that do not use the system. The results of this study show that the smart monitoring and watering system can function properly and maximize the condition of the plant media compared to those that do not use the system. The system can control soil moisture levels with an average error of 3.73% and air temperature with an average error of 1.03%. The results of the system by comparing plants that do not use the system combined with greenhouses can protect plants from extreme weather such as heat, rain, pests, and lack of wild plant growth so that plants look lush, lush, and grow quickly to minimize farmer crop failure. It is easier for farmers to monitor using the Blynk IoT application.